Music, health, and wellbeing - MacDonald, Raymond A. R.; Kreutz, Gunter, 1964-; Mitchell, Laura (Oxford : Oxford University Press, 2012)
Music has a universal and timeless potential to influence how we feel, yet, only recently, have researchers begun to explore and understand the positive effects that music can have on our wellbeing. This text brings together research from a number of disciplines to explore the relationship between music, health and wellbeing.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Music -- Psychological aspects; Music -- Social aspects; Music therapy; Well-being.